An Approach to Schoenberg's Twelve-Tone Method from Schopenhauer's Musical Metaphysics - Mora Calvo, Manuel (2025)
This article arises from a fundamental question: How could twelve-tone music be conceived within Schopenhauer's philosophical system? To answer this, the article begins by describing the metaphysical and aesthetic foundation of Schopenhauer's musical conception. Next, some key points of Schoenberg's twelve-tone method are presented, along with its representation in a musical work. Finally, this compositional method is introduced into that philosophical system, leading to two mutually exclusive interpretations: 1- Twelve-tone music as music that produces suffering (related to the minor key). 2- Twelve-tone music as noise.